Ø¯ÙˆØ± Ø§Ù„Ø¹Ù‚ÙˆØ¨Ø© Ù„ØªØ±Ù‚ÙŠØ© Ù…Ù‡Ø§Ø±Ø© ÙƒÙ„Ø§Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ( Ø¯Ø±Ø§Ø³Ø© Ø§Ù„ØØ§Ù„Ø©ØŒ Ù„Ø·Ù„Ø§Ø¨ Ù…Ø¨Ù†ÙŠ Ø³ØªÙŠ Ø¹Ø§Ø¦Ø´Ø© ÙÙŠ Ù…Ø¹Ù‡Ø¯ ÙˆØ§Ù„ÙŠ ØµØ§Ø¹Ø§ Ø¹Ø§Ø¨Ø± ÙÙˆÙ†ÙˆØ±ÙˆØºØ§ Ù„Ù„ØªØ±Ø¨ÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ©) - Siti Nuzulul Fitriana; Mahmud Fauzi (Program Studi Pendidikan Bahasa Arab, 2020)
The Role of Punishment at Rayyon siti Aisyah in Improving Arabic Language Skills at the Wali Songo Ngabar Islamic Boarding School to discipline students sometimes has to be matched by penalties for some forms of violations or mistakes committed by the students. The goal is to give punishment to the santri to encourage the students to consciously prevent mistakes, if it is not able to awaken the santri, then decisive action must be taken to resolve the santri's problems correctly. Santri are punished because education is not torture, because students must receive education, including punishment as one of the methods at the Islamic Boarding School. the language because language is a crown that needs to be maintained in order to remain beautiful